2023
DOI: 10.1002/ldr.4589
|View full text |Cite
|
Sign up to set email alerts
|

Effects of straw returning and nitrogen addition on soil quality of a coastal saline soil: A field study of four consecutive wheat‐maize cycles

Abstract: The effects of different straw returning and nitrogen addition levels on soil quality are important for proper coastal saline soil remediation. However, relatively little is understood concerning the remediation effects, especially, on long‐term effects and mineral composition and microstructures of coastal saline soil. Two maize/wheat straw returning levels [1.0 × 104 kg ha−1 (2S) and 5.0 × 103 kg ha−1 (S)] and three inorganic nitrogen addition levels [300 kg ha−1 (N2), 150 kg ha−1 (N) and 75 kg ha−1 (N1/2)]—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
2
4
0
Order By: Relevance
“…The recovery rate of soybean straw-derived nitrogen was significantly greater than that of corn straw-derivednitrogen (Figure 11) (p < 0.05), and the recovery rate under low straw application was significantly greater than that under high straw application. Conversely, the rates of undecomposed and loss of soybean straw were significantly lower than those of corn straw Straw return effectively promoted the formation of macro-aggregates, which was consistent with the results of previous research (Yang et al, 2022). This is mainly attributed to the release of organic matter upon straw degradation (Yuan et al, 2023).…”
Section: Distribution Of Straw-derived Nitrogen In Soil and Plantssupporting
confidence: 90%
See 1 more Smart Citation
“…The recovery rate of soybean straw-derived nitrogen was significantly greater than that of corn straw-derivednitrogen (Figure 11) (p < 0.05), and the recovery rate under low straw application was significantly greater than that under high straw application. Conversely, the rates of undecomposed and loss of soybean straw were significantly lower than those of corn straw Straw return effectively promoted the formation of macro-aggregates, which was consistent with the results of previous research (Yang et al, 2022). This is mainly attributed to the release of organic matter upon straw degradation (Yuan et al, 2023).…”
Section: Distribution Of Straw-derived Nitrogen In Soil and Plantssupporting
confidence: 90%
“…Soybean and corn straw have different chemical characteristics (e.g., nutrient content and C/N ratio), which affect the decomposition rate of the straws and the uptake and utilization rate of nitrogen from the straw by subsequent wheat crops due to differences in the nutrients available for microbial growth. Relevant studies have focused on the impact of straw return on the distribution of soil aggregates and the relative change in aggregate‐associated nitrogen content (Xie et al, 2019; Yang et al, 2022). There are few comprehensive studies on the retention of straw‐derived nitrogen by different soil aggregates and the utilization characteristics of straw‐derived nitrogen in subsequent crops via isotope tracing technology, and the straw types mostly include the three major grain crops.…”
Section: Introductionmentioning
confidence: 99%
“…Returned straw decomposition is a complex and lengthy process, involving a combination of physical, chemical, and microbial activities [43,44]. Due to its inherent biochemical stability, the steps of straw decomposition are characterized by several stages.…”
Section: Decomposition Of Returned Strawmentioning
confidence: 99%
“…A soil column experiment conducted by Liao et al [49] showed that treatment with desulfurized gypsum and decomposed straw could significantly reduce the soil salinity of sodic saline soil after leaching. The simultaneous application of straw returning and nitrogen fertilizer improved the properties of the Shandong coastal saline soil and reduced the soil salinity by 27.08% [50]. Straw returning can also optimize the root growth environment by changing water and salt migration, soil porosity, and aggregate size distribution in the soil layer [51,52].…”
Section: Effects Of Straw Returning On Saline Soil Propertiesmentioning
confidence: 99%